Estimation of Trace Elements (Zinc and Copper) in Serum of Multiple Sclerosis Patients in Baghdad City (Iraqi Journal of Medical Sciences, 2023)
Background: Multiple Sclerosis (MS) also known as demyelinating disease, is a condition in which the insulating coverings of nerve cells in the brain and spinal cord are damaged. This injury impairs the nervous system's ability to transfer messages, resulting in a variety of signs and symptoms, including physical, mental, and psychiatric issues. Double vision, blindness in one eye, muscle weakness, and problems with sensation or coordination are all possible symptoms. MS comes in a variety of ways, with new symptoms appearing in isolated attacks (relapsing forms) or gradually over time (progressive forms), the progressive forms symptoms may go away completely between attacks. The exact cause is unknown.Objective: To determine trace elements (zinc and copper) and discuss their relation and effect on MS patients.Methods: The study was performed during the period March 2021 to August 2021, involved 50 samples divided into two groups the first 25 samples from normal individuals (16 males and 9 females) and the second 25 sample of MS patients (12 males and 13 females) collected with help of (Sa'ad Al-Watrai Hospital), (Neuroscience Hospital) in Baghdad City. Samples obtained as serum due to venipuncture considering that patients did not use any treatment during the period of samples collection that may affect analysis results other feature like age, gender and other chronic disease has been recorded in this study.Results: The patients with progressive MS disease showed significant higher copper level than non-progressive MS patients and control samples, when we compare it with control group p =
Keywords: Multiple Sclerosis; Copper Cu; Zinc Zn